Persistent inequality: contemporary inequality in a historical context - Breen, R (Oxford University Press, 2024)
My goal in this commentary is to complement the findings in the article on Education Inequalities by Christine Farquharson, Sandra McNally and Imran Tahir with some general remarks which will provide a context and framework for understanding educational inequalities in Britain. I make five main points, summarized at the start of each section of the commentary.